Persistence of an epidemic cluster of Rhodotorula mucilaginosa in multiple geographic regions in China and the emergence of a 5-flucytosine resistant clone. Issue 1 (31st December 2022) - Huang, Jing-Jing; Chen, Xin-Fei; Tsui, Clement K.M.; Pang, Chong-Jie; Hu, Zhi-Dong; Shi, Yi; Wang, Wei-Ping; Cui, Lan-Ying; Xiao, Yu-Ling; Gong, Jie; Fan, Xin; Li, Ying-Xing; et al.
ABSTRACT: Rhodotorula mucilaginosa, an environmental yeast widely used in industry and agriculture, is also an opportunistic pathogen resistant to multi-antifungals. During the national surveillance in China, R. mucilaginosa has been documented from various hospitals and regions. At present, the molecular epidemiology of invasive infections caused by R. mucilaginosa and their resistance profiles to antifungals were unknown. Here we collected 49 strains from four hospitals located in different geographic regions from 2009 to 2019 in China, determined their genotypes using different molecular markers and quantified susceptibilities to various antifungals. Sequencing of ITS and D1/D2 regions in rDNA indicated that 73.5% (36/49) of clinical strains belong to same sequence type (rDNA type 2). Microsatellite (MT) genotyping with 15 (recently developed) tandem repeat loci identified 5 epidemic MT types, which accounted for 44.9% (22/49) of clinical strains, as well as 27 sporadic MT types. Microsatellite data indicated that the presence of an epidemic cluster including 35 strains (71.4%) repeatedly isolated in four hospitals for eight years. Single nucleotide variants (SNVs) from the whole genome sequence data also supported the clustering of these epidemic strains due to low pairwise distance. In addition, phylogenetic analysis of SNVs from these clinical strains, together with environmental and animal strains showed that the closely related epidemic cluster strains may be opportunistic, zoonotic pathogens. Also, molecular data indicated a possible clonal transmission of pan echinocandins-azoles-5-flucytosine resistant R. mucilaginosa strains in hospital H01. Our study demonstrated that R. mucilaginosa is a multi-drug resistant pathogen with the ability to cause nosocomial infection.